2019
DOI: 10.3892/mmr.2019.10596
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of STAT3‑targeted small interfering RNA and AZD0530 against glioblastoma in�vitro and in�vivo

Abstract: The aim of this study was to explore the synergistic effect of signal transducer and activator of transcription 3 (STaT3)-targeted small interfering (si)rna and aZd0530 against glioblastoma in vitro and in vivo. Glioblastoma cell lines u87 and u251 were divided into four groups and treated with control, lV-STaT3 sirna, aZd0530, and combined lV-STaT3 sirna with aZd0530, respectively. The proliferation and apoptotic capacity of glioblastoma cells was assessed by Cell Counting Kit-8 and double staining flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Pre-clinical trials from 2018, 2019, and 2023 testing new formulations with saracatinib in clear-cell renal carcinoma (ccRCCs) [80], glioblastoma [81], and castration-resistant prostate cancer (CRPC) [82], respectively, were also performed. Specifically, combined therapy with saracatinib and GDC-0941 (an inhibitor of PI3K) inhibits cell growth, and invasion, and promotes cell death in renal tumour cell lines [80].…”
Section: Saracatinib Returns To Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical trials from 2018, 2019, and 2023 testing new formulations with saracatinib in clear-cell renal carcinoma (ccRCCs) [80], glioblastoma [81], and castration-resistant prostate cancer (CRPC) [82], respectively, were also performed. Specifically, combined therapy with saracatinib and GDC-0941 (an inhibitor of PI3K) inhibits cell growth, and invasion, and promotes cell death in renal tumour cell lines [80].…”
Section: Saracatinib Returns To Cancer Treatmentmentioning
confidence: 99%
“…Specifically, combined therapy with saracatinib and GDC-0941 (an inhibitor of PI3K) inhibits cell growth, and invasion, and promotes cell death in renal tumour cell lines [80]. For glioblastoma, in vitro and in vivo trials demonstrated that a combination of Lentivirus vectors containing siRNAtargeted STAT3 (LV-STAT3 siRNA) and AZD0530 has a synergistic effect, inhibiting proliferation and inducing the apoptosis of glioblastoma cells and tumour size reduction [81]. Encouraging in vitro results were also produced in the pre-clinical trial performed in CRPC cells, where the combined therapy of saracatinib and enzalutamide (a second-generation hormonal drug given to men with CRPR) resulted in a reduction in DNA replication and the subsequent increase of apoptosis in a subset of CRPC cells, including those positive for androgen receptor-full length and androgen receptor splice variants (AR-FL+/AR-V+) [82].…”
Section: Saracatinib Returns To Cancer Treatmentmentioning
confidence: 99%
“…For example, AZD0530 is a dual inhibitor of Src family kinases/Abl, inhibiting Src activation and preventing cell growth by inducing G1/S cell cycle arrest (Nygaard et al, 2015). The combined treatment of LV-STAT3 siRNA and AZD0530 shows better effects in inhibiting the proliferation and inducing the apoptosis of GBM cells than using LV-STAT3 siRNA or AZD0530 alone (Liu et al, 2019). Similarly, Pang and colleagues used self-assembling fluorescent virus-like particle/RNAi nano-complexes to downregulate the hepatocyte growth factor receptor gene, inhibiting the DNA repair mechanism.…”
Section: Co-delivery Of Small Interfering Rna and Anti-cancer Compoundsmentioning
confidence: 99%
“…A combined therapy increased the apoptotic rate of GBM cells in vitro and decreased tumor growth in vivo more efficiently as compared with the single treatments. However, saracatinib in vivo was less effective, possibly because of drug metabolism and tumor drug resistance, highlighting how much more needs to be done to improve drug therapy [ 115 ].…”
Section: Targeting Src In Glioblastomamentioning
confidence: 99%